2014
DOI: 10.1116/1.4901877
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of antireflection structure film by roll-to-roll ultraviolet nanoimprint lithography

Abstract: Antireflection (AR) films are useful in preventing the reflection of light from the displays of mobile phones and tablet computers. In particular, films with an AR structure known as the moth-eye structure show excellent performance in preventing light reflection. In a previous study, the authors reported the fabrication of an AR structure by oxygen ion-beam irradiation of glassy carbon (GC). The fabricated pattern consisted of a series of self-assembled conical structures and it had a low-reflection surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Using replica mold has contributed to improvement the process cost. Moreover our previous study also reported that AR structure film by RTR with replica mold which was fabricated by X433-3 under the feed speed of 1.8 m/min [5] . However AR structure is delicate and fragile because it is a fine and complex pattern.…”
Section: Introductionmentioning
confidence: 94%
“…Using replica mold has contributed to improvement the process cost. Moreover our previous study also reported that AR structure film by RTR with replica mold which was fabricated by X433-3 under the feed speed of 1.8 m/min [5] . However AR structure is delicate and fragile because it is a fine and complex pattern.…”
Section: Introductionmentioning
confidence: 94%
“…First, the UV-curable resin (PARQUIT OEX-028-X433-3, hereafter X433-3; AUTEX Co., Ltd., Tokyo) was placed on two types of GC master molds [22]. Subsequently, the resin layer was covered with a polyester film (Cosmoshine A4300; Toyobo Co. Ltd., Osaka) and pressed at 0.3 MPa, which was cured using UV irradiation.…”
Section: Methodsmentioning
confidence: 99%
“…Roll-to-roll (R2R) nanoimprint lithography (NIL) enables large-area nanopatterning either on a rigid or flexible substrate by the continuous imprinting of the nanoscale pattern upon a polymeric resin film based on the pressurized rolling of a mold-bearing roll [ 1 4 ]. A wide choice of substrate materials, large processable area, and high speed of R2R NIL provide a unique methodology for the scalable and practical fabrication of many flexible and large-area applications ranging from optical and photonic components such as wire-grid polarizers [ 5 , 6 ], metastructured optical filters [ 7 ], and antireflection films [ 8 ] through energy devices [ 9 ] to plasmonic sensors [ 10 ]. A successful R2R NIL is a combination of a well-prepared flexible mold that is large enough to wrap around the roll, a well-formulated resin that is suitable for high-speed R2R NIL with quick curing and smooth demolding, and a reliable resin coating method that can afford continuous R2R processing principle.…”
Section: Introductionmentioning
confidence: 99%